EVALUASI PENGGUNAAN PERMODALAN NASIONAL MADANI MELALUI PROGRAM MEMBINA EKONOMI KELUARGA SEJAHTERA BAGI ISTRI NELAYAN DI DESA BAJO INDAH KECAMATAN SOROPIA SULAWESI TENGGARA - Kiky Restiyanty; Sarini Yusuf; Akhmad Mansyur (UNIVERSITAS HALU OLEO, 2022)
Fishermen's wives in Bajo Indah Village Soropia South East Sulawesi have been experiencing some difficulties to meet family needs solely from their husband income. Therefore, they joined the group receiving assistance from National Civil Investment Fund initiated by Indonesian government in 1999 to support micro and small corporations.Assistance is provided in the form of unsecured loans, and is returned within 25 or up to 50 weeks. This research aims to determine the impact of venture capital assistance from this fund to fishermen's wives in Bajo Indah Village South East Sulawesi. This research was conducted in December 2020. This study used census techniques and purposive sampling, with the number of respondents as many as 14 people (13 capital assistance recipients and 1 person from the fund provider). The data were obtained through observation, interviews, and documentation. Primary data such as fund allocation and usage were obtained through interviews using questionnaires whereas secondary data werefrom written reports on capital assistance to fishermen’s wives, books, journals, websites and print media as well as online media. The data obtained were then analyzed using qualitative descriptive data analysis. There were two types of micro and small businesses venture that was found in the village before capital assistance include single fishery and non-fishery business. After receiving capital assistance, there was a mixed business of fishery and non-fishery emerged in one household. This study found mixed type of business wasa dominant form of venture capital assistance utilization. In general, the fishermen wife received IDR. 6,670,000 as investment capital and IDR. 6,798,000 as working capital. The income of fishermen's wives after receiving business capital assistance increased by an average of IDR 7,733,333/month or by 33% compared to before receiving business capital assistance, which was IDR 4,975,000. This study indicated that business capital assistance from National Civil Investment Fund positively impacted the income of fishermen household in Bajo Indah Village through generating alternative livelihood that was run by fishermen's wife. Keywords: Assistance, Capital, Fishermen, Household